If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) + 5(x + 4) = 3(x + 7) + -1x + 6 Reorder the terms: 2(-1 + 3x) + 5(x + 4) = 3(x + 7) + -1x + 6 (-1 * 2 + 3x * 2) + 5(x + 4) = 3(x + 7) + -1x + 6 (-2 + 6x) + 5(x + 4) = 3(x + 7) + -1x + 6 Reorder the terms: -2 + 6x + 5(4 + x) = 3(x + 7) + -1x + 6 -2 + 6x + (4 * 5 + x * 5) = 3(x + 7) + -1x + 6 -2 + 6x + (20 + 5x) = 3(x + 7) + -1x + 6 Reorder the terms: -2 + 20 + 6x + 5x = 3(x + 7) + -1x + 6 Combine like terms: -2 + 20 = 18 18 + 6x + 5x = 3(x + 7) + -1x + 6 Combine like terms: 6x + 5x = 11x 18 + 11x = 3(x + 7) + -1x + 6 Reorder the terms: 18 + 11x = 3(7 + x) + -1x + 6 18 + 11x = (7 * 3 + x * 3) + -1x + 6 18 + 11x = (21 + 3x) + -1x + 6 Reorder the terms: 18 + 11x = 21 + 6 + 3x + -1x Combine like terms: 21 + 6 = 27 18 + 11x = 27 + 3x + -1x Combine like terms: 3x + -1x = 2x 18 + 11x = 27 + 2x Solving 18 + 11x = 27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18 + 11x + -2x = 27 + 2x + -2x Combine like terms: 11x + -2x = 9x 18 + 9x = 27 + 2x + -2x Combine like terms: 2x + -2x = 0 18 + 9x = 27 + 0 18 + 9x = 27 Add '-18' to each side of the equation. 18 + -18 + 9x = 27 + -18 Combine like terms: 18 + -18 = 0 0 + 9x = 27 + -18 9x = 27 + -18 Combine like terms: 27 + -18 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| -6v-(1+8v)=-113 | | 3x-3=3[7-x] | | 27+4+61=14x+8 | | 0.15-0.01(x+1)=0.02(2-x) | | 7x-(-1)=-4 | | 500x+x^2=1000 | | 295+39n=350+33n | | 9.2x-8.8= | | 4(x+5)-2x=22 | | 5.00+.75x=6x | | for((5.6)(5.6))+((12)(12))=((c)(c)) | | .75(6j+9)=3j+7 | | -3n-4+n=2 | | (18X+27)(X^4+6x^3+9x^2)=0 | | 24=2l | | 12c+6c=39 | | 7x(-5)=-25 | | 5+.75m=6m | | 2x+20+x= | | -15x+2(4x-7)=-16-6x | | 159+20x-1=59x+2 | | 5(3x-1)+5=-60 | | 5x=5(-4+3x) | | 0=125+5.2t-4.9t^2 | | 6(-1-7r)=-6-r | | 6x-x=5x+30 | | SOLVEforlP=2l+2w | | 7x+4q=5 | | -6x+2(x-3)=30+2x | | (x+5)2-1=0 | | 7x-5=-25 | | -4.8x-0.12= |